2010
DOI: 10.1002/14651858.cd006542.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating traumatised permanent front teeth: avulsed (knocked out) and replanted

Abstract: The available evidence suggests that extra-oral endodontics is not detrimental for teeth replanted after more than 60 minutes dry time. Studies with moderate/high risk of bias indicate that soaking in thymosin alpha 1 and gentamycin sulphate followed by hyperbaric oxygen may be advantageous however, they have not previously been reported as interventions for avulsed teeth and need further validation. More evidence with low risk of bias is required and, with the low incidence of avulsed teeth, collaborative mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
0
27
0
6
Order By: Relevance
“…The evidence to support different treatment interventions provided by clinicians is limited. A recent Cochrane review (5) identified three randomized controlled trials that were eligible for inclusion. Two of the studies were at high risk, with the third categorized as moderate risk of bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence to support different treatment interventions provided by clinicians is limited. A recent Cochrane review (5) identified three randomized controlled trials that were eligible for inclusion. Two of the studies were at high risk, with the third categorized as moderate risk of bias.…”
mentioning
confidence: 99%
“…As avulsion injuries present relatively infrequently even to specialist centres (2, 3), a multi-centre design would be required. The Cochrane review (5) was unable to identify any multi-centre randomized controlled trials (m-cRCT) teeth.…”
mentioning
confidence: 99%
“…This highlights the need for consensus on the minimum period of follow up for TDI. The two Cochrane reviews in dental traumatology have identified that for periodontal healing, this period should be a minimum of 12 months (1,14). This time period, however, is too short to collect robust data for outcomes such as tooth loss (24).…”
Section: Discussionmentioning
confidence: 99%
“…Arrangements were made to translate and assess studies that were not published in English (13). One of the authors (PD) has been involved with a number of Cochrane reviews, and research papers translated for these reviews were also used where appropriate in this publication (1,14).…”
Section: Languagementioning
confidence: 99%
See 1 more Smart Citation